The exaltation of eucharistic doctrine and other catholic dogmas in the trono de octavas of seville cathedral: an iconographical study. (2012)
Through an iconographic, historical and symbolic studythe Trono de Octavas of Seville Cathedral, one of the mostrepresentative works of art of the city, this paper analyzesthe importance of the Council of Trento in Seville´s 17thand 18th century art.